2015
DOI: 10.3892/ol.2015.3138
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-5′-nucleotidase expression is associated with the progression of renal cell carcinoma

Abstract: Abstract. Renal cell carcinoma (RCC) is a common tissue tumor that occurs across all age groups and has become one of the types of cancer with the fastest increasing incidence. Due to the resistance of RCC chemo-and radiotherapy, surgery is the only currently effective treatment. Therefore, specific markers for the diagnosis and prognosis of RCC are expected to result in novel methods of treatment. Ecto-5'-nucleotidase, also termed cluster of differentiation (CD)73, is a protein that is activated in several ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…In this study, we identified CD73 as a specific cell surface biomarker of ccRCC CSCs basing on our previous studies [ 26 , 27 ] and discovered the association of CD73 intensive expression levels with ccRCC tumor formation by using siRNA technology. To the best of our knowledge, this represents the first identification of CD73 as a cell surface biomarker for ccRCC CSCs and also the first demonstration of the involvement of CD73 in ccRCC progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified CD73 as a specific cell surface biomarker of ccRCC CSCs basing on our previous studies [ 26 , 27 ] and discovered the association of CD73 intensive expression levels with ccRCC tumor formation by using siRNA technology. To the best of our knowledge, this represents the first identification of CD73 as a cell surface biomarker for ccRCC CSCs and also the first demonstration of the involvement of CD73 in ccRCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has recently identified, with rhodamine-123 (Rho) staining and cell sorting from human RCC cell line 786-O, that a small subset of Rho high cells have stem-like characteristics [ 26 ]. Also, we found that the level of Ecto-5′-nucleotidase (CD73) expression in clinical specimens was associated with the aggressiveness of ccRCC [ 27 ]. So, in this study, we verified that CD73 expression was highly associated with positive Rho staining, and it may be a specific biomarker of ccRCC CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al analyzed CD73 expression by IHC in patients with ccRCC, the majority of whom had localized Open access (T1-4, N0, M0) disease. 22 Nearly half of tumors (48%) expressed CD73, which was associated with high tumor grade and T stage. In our prior work in RCC, we observed CD73 expression in 19% of primary tumors and that expression was significantly more common in metastatic tumor samples (67%).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Lu et al reported that high CD73 expression was found in 45.60% of patients with gastric cancer [ 11 ]. Yu and colleagues also found that 47.20% of renal cell carcinoma highly expressed CD73 [ 22 ]. Of note, Hoon et al collected 167 patients with epithelial ovarian cancer and found that 70.1% of patients showed positive expression for CD73 while data from Oncomine showed that ovarian cancer had low CD73 expression level.…”
Section: Discussionmentioning
confidence: 99%